2021
DOI: 10.1007/s00125-021-05405-7
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes induces dysregulation of microRNAs associated with survival, proliferation and self-renewal in cardiac progenitor cells

Abstract: Aims/hypothesis Diabetes mellitus causes a progressive loss of functional efficacy in stem cells, including cardiac progenitor cells (CPCs). The underlying molecular mechanism is still not known. MicroRNAs (miRNAs) are small, non-coding RNA molecules that regulate genes at the post-transcriptional level. We aimed to determine if diabetes mellitus induces dysregulation of miRNAs in CPCs and to test if in vitro therapeutic modulation of miRNAs would improve the functions of diabetic CPCs. Methods CPCs were isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…MiR-30b-5p overexpression could reduce intracellular lipid deposition and regulate intracellular lipid metabolism by targeting PPAR-α and GLUT1, thus triggering mitochondrial oxidative phosphorylation, fatty acidbeta-oxidation and synthesis, glucose uptake, and gluconeogenesis. Also, the mucin-type O-glycan biosynthesis pathway (pathway 2) appears solely associated with hsa-miR-30b-5p, which controls a group of isoenzymes that initiate several glycosylation reactions [48][49][50]. Aberrant expression of glycan has been reported in most hematological malignancies, such as AML, myeloproliferative neoplasms, and multiple myeloma, as well in bone-marrow-associated breast cancer cell dissemination [51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…MiR-30b-5p overexpression could reduce intracellular lipid deposition and regulate intracellular lipid metabolism by targeting PPAR-α and GLUT1, thus triggering mitochondrial oxidative phosphorylation, fatty acidbeta-oxidation and synthesis, glucose uptake, and gluconeogenesis. Also, the mucin-type O-glycan biosynthesis pathway (pathway 2) appears solely associated with hsa-miR-30b-5p, which controls a group of isoenzymes that initiate several glycosylation reactions [48][49][50]. Aberrant expression of glycan has been reported in most hematological malignancies, such as AML, myeloproliferative neoplasms, and multiple myeloma, as well in bone-marrow-associated breast cancer cell dissemination [51][52][53].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, miR-30c was induced during adipogenesis but was downregulated in obese adipocytes [113]. Furthermore, diabetes mellitus significantly downregulated miR-30c-5p associated with stem cell survival, proliferation, and differentiation in cardiac progenitor cells [114]. The last of the analysed miRNAs was miR-21,s which was significantly downregulated in insulinresistant adipocytes [115].…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that compared to model group, ZSP induced PI3K/AKT signaling in both mRNA and protein levels. However, it is worth noting that the mRNA expression of PI3K and AKT are inconsistent with the protein expression in the normal group, which may be the result of potential different post-transcriptional regulations between the wt/wt and db/db mice [ 27 ]. Another explain for this phenomenon is that the insulin level in db/db mice is relatively high, and constant stimulation of insulin may also contribute to the elevated PI3K and AKT expression.…”
Section: Discussionmentioning
confidence: 99%